Education and painting the world - Терещенко, Марія; Щербань, Євгенія (Educological discourse, 2013)
The article is devoted to the analysis of concepts psychological world pattern, world view, education and culture. According to the analysis an attempt to represent human development under the influence of educational processes as the development of the world pattern was made.